RESIDUAL EFFECT OF SEWAGE SLUDGE ON SOME CHEMICAL AND GRANULOMETRIC INCEPTISOL ATTRIBUTES - BARCELAR, Claudia de Azevedo; ROCHA, Aline Alinéia; de LIMA, Marcelo Ricardo; POHLMANN, Marcos (Scientia Agraria, 2001)
The purpose of this work was to evaluate the residual effect of sewage sludge on chemical and granulometric Inceptisol attributes. To achieve this purpose an experiment has been conducted since 1995 at the Canguiri Experimental Station Center, in Pinhais, PR. The selected treatments were no fertilization, mineral fertilization, and organic fertilization with sewage sludge (32, 64 and 96 m3.ha-1), with four replications. The soil samples were collect in 1998 at the following depths: 0-5, 5-10, 10-20 and 20-40 cm. The evaluations consisted of: exchangeable Ca, Mg, K Al, H+Al; available P; organic C; pH in CaCl2; organic matter, total and mineral CEC; sand, loam and clay. No significant results were observed in organic C on the studied depth, or exchangeable Ca on the depth 0-5 and 10-20 cm. There was no significant effect of the sludge on exchangeable Mg and K, available P, H+Al, and total, clay and organic CEC. The pH value increased with addition of sewage sludge on the depth 0-5 and 5-10 cm.